Sosialisasi Pentingnya Integritas Struktur Kapal Kayu Dalam Penjaminan Keselamatan : Masyakarat Sasaran Kelompok Pengrajin Kapal Kayu di Takalar - Hamzah Hamzah Hamzah; Ganding Sitepu '; Andi Ardianti .; Mansyur Hasbullah .; Rosmani .; M. Rizal Firmansyah .; Wahyuddin .; Muhammad Akbar Asis . (Faculty of Engineering UNHAS, 2022)
The operational activities of wooden ships are classified as very high so that the production of wooden boats still survives today, one of the groups of craftsmen in Takalar Regency is the